High-resolution sequence stratigraphy of the Ponta do Mel Formation, Potiguar Basin, Brazil: Insights into shallow-marine carbonate reservoir zonation and characterisation - A.J.C. Magalhães; A.H. Melo; G.J.S. Terra; D.G.C. Fragoso; U.M. Soares; F.P. Lima-Filho (Petroleum Research)
This comprehensive study establishes a novel high-resolution sequence stratigraphic framework for a shallow, warm, land-tied carbonate-rimmed shelf represented by the Ponta do Mel Formation. Integration of cores and cuttings with seismic and well-log data provides the detailed subsurface stratigraphic framework encompassing two fourth-order genetic sequences. The high-resolution approach unveiled the step-by-step depositional and diagenetic evolution of the Ponta do Mel Formation at the fourth-order systems tracts scale and established the reservoir zonation. In each zone, the lateral contact between high-energy outer shelf and shelf rim potential reservoirs and low-energy inner shelf deposits constitutes critical reservoir heterogeneities that may affect production planning and development projects. Moreover, the reservoir scale enabled discussion on the controls on deposition, high-resolution sequence architecture, diagenesis, and insight into the zonation and characterisation of similar oil and gas reservoirs worldwide.